The New 2021 CKD-EPI Equation Without Race in a European Cohort of Renal Transplanted Patients. Issue 12 (2nd August 2022) - Delanaye, Pierre; Masson, Ingrid; Maillard, Nicolas; Pottel, Hans; Mariat, Christophe
Abstract : Background: Whether the new chronic kidney disease-epidemiology (CKD-EPI) equation without the race variable remains accurate enough for glomerular filtration rate (GFR) estimation in non-US kidney transplant recipients (KTRs) is unclear. We sought to compare the predictive performance between this equation and the classical CKD-EPI equation in a French cohort of KTRs. We also evaluated the performance of the European Kidney Function Consortium (EKFC) equation, an estimate that has proved very accurate in nontransplant patients and that does not include race variable. Methods: We retrospectively selected 489 KTRs for whom GFR was measured by inulin clearance. Performances of GFR equations were compared according to median bias, imprecision, and accuracy within 30% (P30) and 20% (P20). Differences in P20/P30 were tested using the exact McNemar test. Results: Although the 4 equations exhibited a similar level of imprecision, the bias of the new CKD-EPI equation was +5.5 (4.0; 6.6) mL/min/1.73 m², much higher than the bias of the classical CKD-EPI, EKFC, and Modified Diet in Renal Diseases (MDRD) equation (2.4 [1.7;3.5], 2.2 [1.1;3.1], and −0.5 [−1.5; 1.0] mL/min/1.73 m², respectively). The new CKD-EPI equation was significantly less accurate with a P30 of 68.3% as compared with 74.2%, 75.3%, and 77.1% for the classical CKD-EPI, EKFC, and MDRD equation, respectively. The EKFC equation outperformed both versions of the CKD-EPI equation in terms of P20. Conclusions: The new CKD-EPI equation is suboptimal for the care and follow-up of European transplanted patients. The EKFC equation shows at least a similar performance to the MDRD and the classical CKD-EPI equation. Further validation of the EKFC equation in KTRs from a diverse ethnic background is needed. Abstract :